Agency Relations, Accountability, and Their Relation to Local Government Public Value Creation - Samel W. Ririhena; Yumiad Fernando Richard (International Journal of Science and Society, 2022)
The purpose of this study is to analyze the relationship between agency, accountability, and their relationship to the creation of local government public value. The method used to compile this research is a survey of academic literature in the field of public administration that is relevant to the research theme. The results obtained from this study indicate that in the administration of local government there are agency relationships and problems. In addition, local government accountability is still not optimal. Therefore, in the future, local governments need to prioritize two-way relationships, accountability models, and public values.